Kurikulum IPS Berorientasi Alam: Kajian Diversifikasi Kurikulum untuk Penguatan Karakter Empati Lingkungan - Pernantah, Piki Setri (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
The development of a social studies curriculum that is nature-oriented and makes nature a laboratory for social studies learning can be implemented as an effort to strengthen students' environmentally empathetic character. This effort provides an opportunity for students to study and understand the natural environment in depth to develop an understanding of the importance of protecting and preserving nature as well as the social impacts of human interaction with the environment. There are several approaches in the nature-oriented social sciences curriculum to strengthen students' environmentally empathetic character, such as content integration, environmental projects, field trips, community collaboration, and even mini research that students can carry out to encourage the formation of environmentally conscious characters, ready to face global challenges, and contribute on sustainable development.